Основы физической химии. Теория и задачи учебное пособие - Еремин В. В. Вадим Владимирович; Каргов С. И. Сергей Игоревич; Успенская И. А. Ирина Александровна; Кузьменко Н. Е. Николай Егорович; Лунин В. В. Валерий Васильевич (Классический университетский учебник)
Авторы указаны на об. тит. л.